Global epidemiology of yaws: a systematic review. Issue 6 (June 2015) - Mitjà, Oriol; Marks, Michael; Konan, Diby J P; Ayelo, Gilbert; Gonzalez-Beiras, Camila; Boua, Bernard; Houinei, Wendy; Kobara, Yiragnima; Tabah, Earnest N; Nsiire, Agana; Obvala, Damas; Taleo, Fasiah; et al.
Summary: Background: To achieve yaws eradication, the use of the new WHO strategy of initial mass treatment with azithromycin and surveillance twice a year needs to be extended everywhere the disease occurs. However, the geographic scope of the disease is unknown. We aimed to synthesise published and unpublished work to update the reported number of people with yaws at national and subnational levels and to estimate at-risk populations. Methods: We searched PubMed and WHO databases to identify published data for prevalence of active and latent yaws from Jan 1, 1990, to Dec 31, 2014. We also searched for ongoing or recently completed unpublished studies from the WHO yaws surveillance network. We estimated yaws prevalence (and 95% CIs). We collected yaws incidence data from official national surveillance programmes at the first administrative level from Jan 1, 2010, to Dec 31, 2013, and we used total population data at the second administrative level to estimate the size of at-risk populations. Findings: We identified 103 records, of which 23 published articles describing 27 studies and four unpublished studies met the inclusion criteria. Prevalence of active disease ranged from 0·31% to 14·54% in yaws-endemic areas, and prevalence of latent yaws ranged from 2·45% to 31·05%. During 2010–13, 256 343 yaws cases were reported to WHO from 13 endemic countries, all of which are low-income and middle-income countries. 215 308 (84%) of 256 343 cases reported to WHO were from three countries—Papua New Guinea, Solomon Islands, and Ghana. We estimated that, in 2012, over 89 million people were living in yaws-endemic districts. Interpretation: Papua New Guinea, Solomon Islands, and Ghana should be the focus of initial efforts at implementing the WHO yaws eradication strategy. Community-based mapping and active surveillance must accompany the implementation of yaws eradication activities. Funding: None.